The Effect of Dosage and Application Time of Liquid Organic Fertilizer From Papaya (POCpy) on The Growth and Production of Soybean Plants (Glycine max L) in Ultisol Oil - Simbolon, Fenty Maimunah; Rahmawati, Rahmawati; Pradana, Diva Anggun; Ginting, Sulaiman; Gunawan, Indra (PT Inovasi Pratama Internasional, 2025)
This study aims to determine the effects of applying papaya liquid organic fertilizer and varying the timing of application on the growth and yield of soybean (Glycine max L.) plants in Ultisol soil. The study employed a factorial randomized block design with two studied factors: 1. The first factor is papaya liquid organic fertilizer (P), which has four treatment levels: P1 = 75 ml/polybag; P2 = 150 ml/polybag; P3 = 225 ml/polybag; and P4 = 300 ml/polybag. The second factor is application time (W), which consists of three treatment levels: The second factor is application time (W), consisting of three treatment levels: W1 = at planting; W2 = one week before planting; and W3 = two weeks before planting. The observed parameters are plant height, number of branches, number of pods per polybag and filled pod weight. The research results indicate that applying liquid organic papaya fertilizer significantly affects the number of branches, number of pods per polybag and filled pod weight. However, it had no significant effect on soybean plant height. The timing of the application treatment non significantly affected plant height, number of branches, number of pods per polibag, filled pod weight. The interaction between the application of liquid organic papaya fertilizer and application time did not significantly affect plant height, number of branches, number of pods per polybag and filled pod weight.